NAFORMA: National Forest Resources Monitoring and Assessment of Tanzania Mainland - Rajala, Tuomas; Heikkinen, Juha; Gogo, Sophia; Ahimbisibwe, Joyce; Bakanga, Geofrey; Chamuya, Nurdin; Garcia Perez, Javier; Kilawe, Edward; Kiluvia, Shani; Morales, David; Nzunda, Emmanuel; Otieno, Jared; et al. (FAO, 2022)
Three options for the sampling design of the field plot clusters of NAFORMA II biophysical survey are compared in this report. Option 1 consists of re-measuring all NAFORMA I field sample plots (3 205 clusters) and Option 2 of re-measuring only those that were established as permanent (848 clusters). The recommended Option 3 is a compromise between these two “extreme” options: Re-measure a subset (1 405 clusters) of NAFORMA I field sample plots including (almost) all permanent clusters and a carefully selected set of other NAFORMA I field plot clusters to obtain a uniform sample within each TFS zone. Design Option 3 has the following features: • Sampling intensity is uniform within each TFS zone. This makes it simple to use the data. For example, mean volumes can be estimated by averages over the plots. • The selected clusters are well-spread over the target population. • The anticipated precision of land-class area and mean wood volume relative to sample size is nearly as good as that of NAFORMA I. • All proposed clusters were measured in NAFORMA I, which enables precise estimation of change based on repeated measurements. The costs and precision were anticipated by utilizing NAFORMA I field data, information about subsequent improvements in the road network, and changes in land-use using satellite imaging derived land-class maps.
Keywords: otanta; tilastotiede; inventointi; national forest inventory